Design and Implementation of a Smart Traffic Light Management System Controlled Wirelessly by Arduino - Alaidi, Abdul Hadi M.; Aljazaery, Ibtisam A.; Alrikabi, Haider TH. Salim; Mahmood, Ibrahim Nasir; Abed, Faisal Theyab (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In Iraq, the number of people who own vehicles has grown up significantly. However, this increment in vehicles number doesn’t accomplished by a study of roads and intersections expansion. As a result, traffic jams became a big problem that led to long waiting time at each intersection, increased car accidents, pollution, and economic problems. To solve this problem a Smart Traffic Light System (STLS) has been implemented using Arduino, camera, IR sensor to overcome traffic jams problems in Kut city – Iraq.